Thermoelectric Conversion of Motorcycle Exhaust Heat into Alternative Electrical Energy: A Mini Review - Pranata, Ragil Tri; Irawan, Nanda Satria; Santosa, Alvian Rizky; Althaf, Muhammad; Adinata, Bintang; Yang, Lee; Sandi, Dianisa Khoirum (Politeknik Negeri Semarang, 2025)
Heat energy can be harnessed as an alternative source for electricity generation, including waste heat from motorcycle exhaust. Thermoelectric technology enables the direct conversion of this waste heat into electrical energy. This mini-review examines the utilization of motorcycle exhaust heat through thermoelectric systems. The findings indicate that exhaust temperatures can activate thermoelectric modules to produce electrical power, which can be used for applications such as motorcycle-mounted cell phone chargers. The generated electricity can also be stored in batteries to power lighting systems. Given Indonesia's high number of motorcycles, this technology shows strong potential for small-scale renewable energy generation, supporting advancements in sustainable energy solutions.